Evolution of paradigms in the study of depression: from a unitary concept to a biopsychosocial model and interdisciplinary approaches - A. N. Kornetov (Бюллетень сибирской медицины)
The review is devoted to the consideration of the history of paradigms in the study of depressive disorders in terms of modern understanding of depression in psychiatry and clinical and medical psychology and its correlation with the biopsychosocial model in medicine. The review also contains works devoted to the study of the prevalence and comorbidity of depressive disorders and their relationship with suicidal behavior. The existing limitations in the study of depressive disorders in psychiatry and clinical psychology and the issues of interdisciplinary integration and interdisciplinary barriers are considered in detail. The review includes publications indexed in the Web of Science, Scopus, Russian Science Citation Index, and PubMed databases. Depression is a major medical and psychological problem due to its widespread prevalence in the general population, in primary care, among patients with various chronic somatic symptom disorders who receive treatment in community and specialized hospitals and clinics, and among clients of psychological centers and social services. In 1996, the Harvard T.H. Chan School of Public Health, based on the materials of the World Health Organization (WHO) and the World Bank, published estimates and prognosis for the prevalence of depressive disorders around the world. According to their data, depression in 1990 was ranked 4th in terms of the severity of the leading causes of the burden of the disease, and according to the baseline scenario of development, by 2020 it should have been ranked 2nd after coronary artery disease. The review is focused on the need to revise the baseline scenario of development and start a new discussion on the study of depressive disorders under new conditions, such as the psychological state of society during the COVID-19 pandemic and lockdown, as well as on the eve of healthcare transition to the 11th Revision of the International Classification of Diseases.